Rekonstruksi Undang-Undang Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat (Analisis Hukum Ekonomi Syariah) - Muhammad Adi Riswan Al-Mubarak; Nurul Iman; Febri Wimpi Hariadi (Musyarakah: Journal of Sharia Economic (MJSE), 2021)
This study aims to determine the reconstruction of Law Number 23 of 2011 concerning Zakat Management and analyze it according to the view of Sharia Economic Law. This research is a normative legal research which is a literature study. Based on the results of the study indicate that Law no. 23 of 2011 on Zakat Management talks more about zakat management institutions, the requirements for establishing LAZ and sanctions for LAZs that do not report their zakat management. This law excludes sanctions for muzakki who do not want to pay their zakat. Even though one of the instruments for increasing income from the increasing potential of zakat is the existence of coercion to muzakki to issue zakat. At least provide legality and legal protection for amil in carrying out the task of collecting zakat from muzakki. Legislation can be said to be good and valid according to law, effective and acceptable to the community and valid for a long time, must be based on the basis of legislation. The basis of the legislation includes 3 foundations, philosophical, sociological and juridical foundations. Law No. 23 of 2011 concerning Zakat Management does not seem to cover a juridical basis because there are no articles that further regulate legality and legal protection for amil in carrying out their duties as zakat collectors for muzakki.